Estratégias didáticas para ensino de física moderna usando leds - Miguez, Maria Luiza (2024)
Themes of Modern and Contemporary Physics are currently already included in the BNCC (Base Nacional Comum Curricular), both in the Science curriculum component in Elementary School and in High School. Motivated by this, there are already several works proposing intervention practices in the classroom on this topic. Despite this, there are still few works that present the results of the application of these proposals. It is also important to note that there are few proposals that use various articulated teaching methodologies. Our proposal is based on Vygotsky’s socio-interactionist theory, which assumes that social interactions are fundamental for greater efficiency in the teaching and learning process, to support and justify the use of methodologies based on experimentation and Peer Instruction questionnaires to promote the teaching of Modern Physics using LEDs. The educational product is a didactic sequence of 06 classes. We start in Class 01 with the classification of materials in terms of electrical conductivity and how it can be modified in semiconductor materials through the doping process. In classes 02 and 03, we introduce the Bohr model and the experimental activity of observing the emission spectra of various light sources, respectively. In Class 04, we introduce the theory of conduction bands, and in Class 05, we introduce the PN junction to justify the functioning of an LED device. We conclude the sequence with an experimental activity in which students must investigate the functioning of an ohmic resistor and an LED and identify the differences in the electrical properties of these devices. Questionnaires were administered in the first two classes to assess students’ prior knowledge, and based on the results, it was possible to verify that students had difficulties assimilating previous content, thus reinforcement was necessary for the progression of the classes. At the end of the first 5 classes, questionnaires were administered using the Peer Instruction methodology, and based on students’ responses, it was possible to evaluate the understanding of the content discussed in the respective class. Furthermore, it was possible to verify through student interactions with each other and with the teacher during the class that the strategies applied were well received by the students. We can conclude that teaching Physics from contextualized situations, using methodologies that place students in less passive positions, can be alternatives to the completely traditional teaching approach.